The Sociology of Greed - Ray, Prasanta, author.
1 online resource (xvi, 182 pages)
Keywords: "The Sociology of Greed examines crises in financial institutions such as banks from the vantage point of the greed of the people at their helm. It offers an intensive analysis of the banking crises under conditions of colonial capitalism in early twentieth-century Bengal that led to institutional and social collapse. Breaking new ground, the book looks at the moral economy of capitalism and money culture by focusing on the victims of banking crises, hitherto unexplored in Western empirical research. Through sociological analyses of political economy, it seamlessly combines archival records, survey and statistical data with literary narratives, realist fiction and performing arts to recount how the greed of bank owners and managers ruined their institutions as well as common people. It argues that greed turns perilous when the state and the market facilitate its agency, and examines the contexts and histories, the indifference of the colonial state, feeble political response, and the consequences for those who were impacted and the losses, especially the refugees, the lower-middle class and women. The volume also re-composes relevant elements of Western sociological scholarship from classical theories to early twenty-first-century financial sociology. An insightful account of the social history of banking in India, this book will greatly interest researchers and scholars in sociology, economics, history and cultural studies."--Provided by publisher.